PENGARUH KURIKULUM PENDIDIKAN, MOTIVASI MAHASISWA DAN KOMPETENSI DOSEN TERHADAP PEMAHAMAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN - Wening Estiningsih (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2014)
Abstract: This study aims to test empirically the phenomenon of understanding of financial statement presentation at the senior colleges in several regions of Depok. empirical studies of the few universities in Depok Region Academic Year 2010/201. There are three independent variables in this study, which consisted of Education Curriculum, Students and Competence Motivation Lecturers. While the dependent variable in this study is understanding “Pernyataan Standar Akuntansi Keuangan (PSAK)” or Statement of Financial Accounting Standards (SFAS) No 1 .The method of analysis of this study using multiple regression analysis and the existence of three independent variables into the basic formation of the three research hypotheses. By using SPSS version 17, for first to third hypothesis proves that the educational curriculum, student motivation and competence of lecturers have a positive influence on students' understanding on the “Pernyataan Standar Akuntansi Keuangan (PSAK)” or Statement of Financial Accounting Standards (SFAS) No 1. These results confirm and support the hypothesis that: (a) there was indeed influence the effectiveness, usefulness and practicality of the education curriculum to students' understanding in presenting the financial statements (IAS 1), (b) there is the influence of responsibility, interest and appreciation reflects the motivation of students to the understanding of students in presenting the financial statements (IAS 1). Key words : Curriculum; Motivation; Competence Lecturer